2008
DOI: 10.1073/pnas.0807225105
|View full text |Cite
|
Sign up to set email alerts
|

A host dicer is required for defective viral RNA production and recombinant virus vector RNA instability for a positive sense RNA virus

Abstract: Defective interfering (DI) RNAs, helper virus-dependent deletion mutant RNAs derived from the parental viral genomic RNA during replication, have been described for most RNA virus taxonomic groups. We now report that DI RNA production in the chestnut blight fungus, Cryphonectria parasitica, persistently infected by virulence-attenuating positive sense RNA hypoviruses, depends on one of two host dicer genes, dcl-2. We further report that nonviral sequences that are rapidly deleted from recombinant hypovirus RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 36 publications
7
81
0
Order By: Relevance
“…Nuss and coworkers demonstrated that the RNA silencing components DCL-2 and AGL-2 are required for the generation of CHV1 DI-RNA species (27,28), and our previous study showed that the existing DI-RNA in EP155 rarely moved to the ⌬dcl-2 recipient side along with helper CHV1 in the lateral transmission assay (17). In the present study, we confirmed this with a virus mutant, CHV1-⌬p69, during RnVV1 coinfection assay in which DI-RNAs appeared only in the EP155 host backgrounds (see the asterisked DI-RNAs in Fig.…”
Section: W1029 Is Infected With a Novel Partitivirus And A Novel Victmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuss and coworkers demonstrated that the RNA silencing components DCL-2 and AGL-2 are required for the generation of CHV1 DI-RNA species (27,28), and our previous study showed that the existing DI-RNA in EP155 rarely moved to the ⌬dcl-2 recipient side along with helper CHV1 in the lateral transmission assay (17). In the present study, we confirmed this with a virus mutant, CHV1-⌬p69, during RnVV1 coinfection assay in which DI-RNAs appeared only in the EP155 host backgrounds (see the asterisked DI-RNAs in Fig.…”
Section: W1029 Is Infected With a Novel Partitivirus And A Novel Victmentioning
confidence: 99%
“…The RNA silencing pathway is able to suppress replication of hypoviruses, mycoreoviruses (26,27), and also a heterologous partitivi-rus (family Partitiviridae) (17). Furthermore, such RNA silencing is required for the generation and maintenance of defective interfering (DI)-RNAs of the prototype hypovirus, Cryphonectria hypovirus 1/EP713 (CHV1-EP713) (27,28).…”
mentioning
confidence: 99%
“…As another model, DI-RNAs efficiently trigger, but are not targeted by, RNA silencing that degrades helper viral mRNAs as an antiviral defense mechanism in plants, leading to symptom attenuation (4,5). Another interesting link between RNA silencing and DI-RNAs has been noted by Nuss and coworkers (6): RNA silencing is associated with the generation of DI-RNA in fungal cells infected with a hypovirus with a (ϩ) singlestranded RNA (ssRNA) genome. They hypothesized that hypovirus RNAs fragmented by the host RNA silencing pathway increase the rate of, and provide substrate for, template switching to produce DI-RNAs.…”
mentioning
confidence: 99%
“…In the present study, applying a transfection technique with purified virus particles that had recently been developed for a partitivirus (22), we were able to obtain a DI-free strain of RnPV2 in an RNA silencing-defective mutant of a heterologous fungus, C. parasitica (6). We report here the molecular and biological properties of RnPV2, focusing on the effects of DI-dsRNA on replication and symptom induction using both natural and experimental host fungi.…”
mentioning
confidence: 99%
“…A similar induction and repression of Dicer gene expression has not yet been reported for infected plants or animals. A surprising role for C. parasitica DCL2 in viral RNA recombination, the production of internally deleted, defective interfering (DI) RNAs and the instability of foreign gene sequences in recombinant RNA virus vectors, was recently demonstrated (17).…”
mentioning
confidence: 99%